Diseño de un sistema de ejercicios para el desarrollo de las capacidades físicas generales en niños de 10 a 11 años en las calles García Moreno y Mejía en la ciudad de Babahoyo - López Sánchez, Marck Anthony (2021)
The following research is entitled: Design of an exercise system for the development of general physical capacities in children aged 10 to 11 years in the streets Gracia Moreno and Mejía in the year 2021, obtained the results of the established diagnosis to detect the problem that is presented at the research site, the main objective of the research is to design a system of physical exercises for the development of the general physical capacities of children from 10 to 11 years of age. In the elaboration of the theoretical framework, information was collected according to the variables, to be scientifically based by consulting scientific articles, theses, books, brochures and a magazine. Instruments such as the physical tests of the Corvette Course, deep trunk flexibility, speed of 50 meters and abdominals in 30 seconds were used. In addition, a survey was applied to the sample of 10 children between 10 and 11 years old from García Moreno and Mejía streets, in the city of Babahoyo, thus giving its due conclusions and recommendations. According to what has been done in the research, the exercise system for the development of general physical capacities in children between 10 and 11 years old from García Moreno and Mejía streets of the city of Babahoyo is designed in the year 2021. This will allow improving the physical condition of the beneficiaries, in addition to this it can serve as a guideline for physical education teachers or coaches to apply it in the context that they require.